2017
DOI: 10.1097/j.pain.0000000000001014
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species affect spinal cell type-specific synaptic plasticity in a model of neuropathic pain

Abstract: Spinal synaptic plasticity is believed to drive central sensitization that underlies the persistent nature of neuropathic pain. Our recent data showed that synaptic plasticity in the dorsal horn is cell type-specific: intense afferent stimulation produced long-term potentiation (LTP) in excitatory spinothalamic tract neurons (STTn), whereas it produced long-term depression (LTD) in inhibitory GABAergic interneurons (GABAn). In addition, reactive oxygen species (ROS) were shown to be involved in LTP in STTn (ST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 42 publications
3
49
0
Order By: Relevance
“… 2 Our previous studies showed that ROS induces and maintains long-term changes in excitatory postsynaptic responses in spinal dorsal horn neurons in a cell type-specific manner, potentiating the responses in excitatory projection neurons but suppressing them in GABAergic inhibitory neurons. 3 At a behavioral level, reducing ROS with scavengers such as phenyl-N-tert-butylnitrone and 4-hydroxy-2,2,6,6-tetramethylpiperidine 1-oxyl (TEMPOL) alleviates neuropathic mechanical pain 4 6 and capsaicin-induced secondary mechanical hypersensitivity that is also attributed to central sensitization. 7 9 …”
Section: Introductionmentioning
confidence: 99%
“… 2 Our previous studies showed that ROS induces and maintains long-term changes in excitatory postsynaptic responses in spinal dorsal horn neurons in a cell type-specific manner, potentiating the responses in excitatory projection neurons but suppressing them in GABAergic inhibitory neurons. 3 At a behavioral level, reducing ROS with scavengers such as phenyl-N-tert-butylnitrone and 4-hydroxy-2,2,6,6-tetramethylpiperidine 1-oxyl (TEMPOL) alleviates neuropathic mechanical pain 4 6 and capsaicin-induced secondary mechanical hypersensitivity that is also attributed to central sensitization. 7 9 …”
Section: Introductionmentioning
confidence: 99%
“…70 Reactive oxygen species (ROS) play a dual role in physiological and pathophysiological reactions, and have been used extensively in different inflammatory and neuropathic pain models. 71,72 Electrophysiological and behavioral studies have been performed to address the role of ROS in the central nucleus of amygdala in a visceral pain model induced by intracolonic zymosan. 73 and increased blood pressure and heart rates can be measured by electromyography and surgical implantation of an arterial catheter, respectively.…”
Section: Electrophysiologymentioning
confidence: 99%
“…ROS was identified as a pivotal modulator factor in immune system, neural system, infection and cancer development [ 24 27 ]. ROS homeostasis is essential in the sustain of cells function.…”
Section: Ros and Oxidative Stressmentioning
confidence: 99%